Conceptualization of Strategic Ecosystem in an Emerging Market Banking Industry - Olota, Oluwayomi Omotayo; Balogun, Ebenezer; Babawale, Opeyemi (Journal of Humanistic, Management and Social Science Review, 2025)
The interactions between a bank’s operating environment and its strategies are often complex and not easily visible, yet they play a significant role in shaping the bank’s progress. Hence, this study assessed strategic ecosystem and banking performance in emerging market banking industry. Specifically, the study assessed the revolution, characteristics, dimensions, significance as well as problems and prospect of strategic ecosystem on banking performance in emerging markets. The study adopted conceptualization approach by gathering available and related reviews on the study. The study was also based on Adner Ecosystem Strategy Framework. The study found that through the integration of technology, strategic partnerships, regulatory frameworks, and sustainability considerations, banks in emerging markets are evolving their business models to remain competitive, innovative, and inclusive. However, challenges persist, including technological infrastructure gaps, regulatory barriers, financial constraints, low digital literacy, and cyber security risks, all of which can hinder the full potential of these ecosystems. Conclusively, the concept of a strategic ecosystem in banking is both a transformative opportunity and a multi-faceted challenge that must be approached holistically, especially in the context of emerging markets as it offers a promising opportunities for strong bank performance in these markets. Banks therefore should invest in technological infrastructure to fully leverage the benefits of strategic ecosystems as it is essential to invest in upgrading digital infrastructure. Additionally, banks should promote digital literacy and financial education as it is critical to address the issue of low digital literacy.